ANGKA KEBUTUHAN NYATA OPERASI DAN PEMELIHARAAN (AKNOP) DAERAH IRIGASI PATEGUAN KECAMATAN PANDAAN - Suhendro, Deni Eko; Maulidiyah, Afrikhatul (SISTEM Jurnal Ilmu Ilmu Teknik, 2023)
Pateguan Irrigation Area has an area of 1,466 ha with a canal length of 20,835 m is still not sufficient to fulfill the irrigation needs for agricultural land in the region. Due to the existing conditions in the irrigation canals of the Pateguan irrigation area, there is a lot of damage such as leaks and siltation. This is due to the large amount of sediment contained in the irrigation canals which makes the flow of water obstructed. The obstruction of water flow in irrigation canals has a significant impact on the growth and development of plants in agricultural land. Based on these problems, it is necessary to determine the real needs of network operation and maintenance with the aim of knowing how network operation and maintenance activities and the number of needs for operation and maintenance of irrigation networks. The type of research is descriptive qualitative by using the method of site survey, observation and interviews as well as documentation studies and technical data collection to determine the real needs of operation and maintenance of Pateguan Irrigation Area, Pandaan District. Based on the results of the analysis, it is known that the Physical Condition of the Pateguan Irrigation Area is 59.53% and has 40.47% damage, the existing personnel in the Pateguan Irrigation Area is undermanned, because the number of personnel is not in accordance with the Permen PU. The real need for operation and maintenance in the Pateguan Pateguan Irrigation Area is Rp 3.088.362.121,25.